PEMEROLEHAN MORFOLOGI (VERBA) PADA ANAK USIA 3 DAN 4 TAHUN (SUATU KAJIAN NEURO PSIKOLINGUISTIK) - Zherry, Zherry Putria Yanti; Gusriani, Atika (LP2M Universitas Adzkia, 2022)
Abstract The purpose of this study is to describe language acquisition through conversational utterances with families that are used by children aged 3-4 years in speaking in their environment using a morphological level. The occurrence of language development is not related to a person's cognitive development, because intellectual factors greatly affect a person's language skills. The method used in this study is the listening method using an advanced technique in the form of a not-taking technique. The note-taking technique was used as a technique in data collection. The not-taking technique is to record several forms that are relevant to his research from the use of written language. Data collection techniques are carried out through interviews or dialogues and not –taking techniques to reveal the ability to tell stories to the child. The data source used is the voice recording of a 4 year old child named Zahira Syafitri. Mastery of Zahira's language (4 years old) is more directed at imitating sounds or words by those closest to him, the child can repeat what he has heard. At this stage the child begins to develop his language and Zahira is able to pronounce it with the addition of inserts in the form of pel-, mel-, and nyal-. Keywords: Acquisition of morphology (verb), children aged 3 and 4 years